Wafer-Bonded Active/Passive Vertically Coupled Microring Lasers - Hamacher, M. (Institutional Knowledge at Singapore Management University, 2008)
We summarize the results of a European Project entitled WAPITI (Waferbonding and Active Passive Integration Technology and Implementation) dealing with the fabrication and investigation of active/passive vertically coupled ring resonators, wafer bonded on GaAs, and based on full wafer technology. The concept allows for the integration of an active ring laser vertically coupled to a transparent bus waveguide. All necessary layers are grown in a single epitaxial run so that the critical coupling gap can be precisely controlled with the high degree of accuracy of epitaxial growth. One key challenge of the project was to establish a reliable wafer bonding technique using BCB as an intermediate layer. In intensive tests we investigated and quantified the effect of unavoidable shrinkage of the BCB on the overall device performance. Results on cw-operation, low threshold currents of about 8 mA, high side-mode suppression ratios in the range of 40 dB and large signal modulation bandwidths of up to 5 GHz for a radius of 40 μm shows the viability of the integration process.